Kajian Hermeneutika Foto “Phantom” Karya Peter Lik - Nugroho, Yulius Widi (Journal of Contemporary Indonesian Art, 2022)
Interpretation with the hermeneutic theory of the artwork entitled Phantom by Peter Lik which is known as one of the most expensive photographic works. The analytical method used is Gadamer's hermeneutical theory to interpret meaning based on the visual appearance and conceptual background of Phantom. In contemporary photographic works, they are presented as representations of multiple realities which are analyzed using hermeneutic methods. The object of research is interpreted as a text from an image that has layers of meaning whose essence is extracted and identified from the text analysis process and the creation process. The theory of Gadamer is used because it is a philosophical hermeneutic that frees from aesthetic and methodological boundaries, and develops the universal ability of humans to understand. Artwork plays an important role in understanding hermeneutics. Gadamer calls it reproductive art, so that discussion through works of art can take him further to question the interpretation of texts/discourses, history, and traditions. Hermeneutic discussion is a way that allows one to make an understanding of the claim of understanding to give meaning to a work. The results of hermeneutic extraction produce an interpretive study of Phantom's work which is full of meaning from historical studies, social arts, even branding, and success in creating publicity. The study of the Phantom photo object is expected to provide positive benefits for the development of photography, especially academically.